Twentieth-Century European Drama
X, 228 p.
Keywords: This volume offers critical and theoretical perspectives on some of the major figures in European drama in the twentieth century. There are thirteen essays covering Luigi Pirandello, Bertolt Brecht, Stanislaw Witkiewicz, Samuel Beckett, Antonin Artaud, Eugene Ionesco, Jean Anouilh, Fernando Arrabal, Jean Genet, Peter Weiss, Vaclav Havel, comtemporary German theatre, and Dario Fo and Franca Rame. These specially commissioned essays combine contemporary theory with a discussion of the dramatic work of the playwrights who created modern drama in Europe.